Can Third Party Funds, Financing to Deposit Ratio, and Capital Adequacy Influence Murabaha Financing? Study of Islamic Banks in Indonesia - Nanda, Riska (Journal of Accounting Research, Organization and Economics, 2020)
Objective This study aims to examine the effect of the factors that effect murabaha financing in Islamic Commercial Banks in Indonesia for the 2014-2018 period. Design/methodology The population in this study is 13 Islamic Commercial Banks in Indonesia which were established during 2014-2018, resulting in 62 observations. Data were examined using multiple linear regression analysis panel data. Results The results showed that third-party funds, optimizing the distribution of funding and capital adequacy have a joint effect on murabaha financing, third-party funds has a negative effect on murabaha financing, optimizing the distribution of financing that has a positive effect on murabaha financing, capital adequacy has a positive effect on murabaha financing.